2022
DOI: 10.1038/s41420-022-00818-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ADRB2 enhances sensitivity of non-small cell lung cancer to VEGFR2 tyrosine kinase inhibitors

Abstract: Vascular Endothelial Growth Factor Receptor 2 (VEGFR2) tyrosine kinase inhibitors (TKIs) have achieved remarkable clinical progress in the treatment of non-small-cell lung cancer; however, resistance has limited their therapeutic efficacy. Therefore, understanding the mechanisms of VEGF-TKI and ICI resistance will help to develop effective treatment strategies for patients with advanced NSCLC. Our results suggested that treatment with VEGFR2-TKIs upregulated ADRB2 expression in NSCLC cells. Propranolol, a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
7
1
Order By: Relevance
“…Our data clearly demonstrated that either selective or non-selective targeting of the β 2 AR subtype is important to exert antitumor effects in multiple myeloma. We observed a heterogeneous βAR expression and response to β-blocker therapy in the tested multiple myeloma patients' samples, which could potentially be attributed to differences in disease stage, tumor progression, and therapy, as already reported for other cancer types [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…Our data clearly demonstrated that either selective or non-selective targeting of the β 2 AR subtype is important to exert antitumor effects in multiple myeloma. We observed a heterogeneous βAR expression and response to β-blocker therapy in the tested multiple myeloma patients' samples, which could potentially be attributed to differences in disease stage, tumor progression, and therapy, as already reported for other cancer types [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…The ADRB2 gene encodes the beta2-adrenergic receptor ( β 2-AR), which plays a crucial role in facilitating bronchodilation ( 47 ). Studies have shown that targeting ADRB2 could enhance the sensitivity of lung cancer cells to VEGFR2-TKIs ( 48 ), but the protective mechanism of ADRB2 on LUAD has not been mentioned in the literature. The binding of leucine-rich repeat-containing G-protein-coupled receptor 4 ( LGR4 ) to its receptor R-spondin was reported to promote the proliferation and metastasis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…HRH1 protein expression was associated with sensitivity to pemetrexed (Table 2). HRH1 was reported as an apatinib (VEGFR2 inhibitor) upregulated gene and was also associated with neuroactive ligand in NSCLC cells [94]. HRH1 had different prognostic implications in various cancer types [95].…”
Section: Discussionmentioning
confidence: 99%